Effects of nanoparticle size and concentration on optical, toughness, and thermal properties of polycarbonate. Issue 23 (15th February 2019) - Nomai, Jiraporn; Schlarb, Alois K.
ABSTRACT: The influences of size and content of silicon dioxide (SiO2 ) nanoparticles on the morphological, optical, toughness, and thermal properties of polycarbonate (PC) were investigated. The PC nanocomposites were prepared using a twin‐screw extruder followed by injection molding. The scanning electron microscope (SEM) micrographs displayed an adequate level of nano‐SiO2 particle distribution within the PC matrix but still revealed some agglomerated particles. Upon increasing the content of nanoparticles, slightly larger agglomerates formed. These agglomerated particles caused a reduction in material transparency due to light loss via reflection and scattering. However, the incorporation of nano‐SiO2 into the PC matrix greatly improved toughness properties and slightly increased glass‐transition temperature ( T g ), in conjunction with filler content (up to 4 vol %). This was particularly in the case with the smaller sized nano‐SiO2, which not only significantly improved toughness but also enhanced optical properties of the PC nanocomposites. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47634. Abstract :